2013
DOI: 10.1016/j.apsusc.2013.07.131
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength enhancement of silicon Raman scattering by nanoscale laser surface ablation

Abstract: International audienceIn this paper, we produce nanoholes on a silicon surface by laser ablation. Those nanoholes lead to a yield enhancement of light-matter interaction. Performing Raman spectroscopy on silicon, an enhancement of its main Raman mode is observed: it is twice higher with the nanoholes compared to a flat surface. Such a feature appears whatever the excitation wavelength (488, 514.5 and 632.8 nm) and the laser power, revealing a broad band light-matter interaction enhancement. In addition, no cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The substrates exhibit in average $84% monolayer coverage ratio, due to large number of clusters ($16% of total discontinuities). This is still higher than the previously reported 60% ratio when using the standard LB technique [34,35]. The reduction in coverage of monolayer could be attributed to the nature of particles (size, density, degree of functionalization) but is worth reminding here that similar results were obtained for both PS and silica spheres with the same size (1 lm) and the same functionalization (C18).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The substrates exhibit in average $84% monolayer coverage ratio, due to large number of clusters ($16% of total discontinuities). This is still higher than the previously reported 60% ratio when using the standard LB technique [34,35]. The reduction in coverage of monolayer could be attributed to the nature of particles (size, density, degree of functionalization) but is worth reminding here that similar results were obtained for both PS and silica spheres with the same size (1 lm) and the same functionalization (C18).…”
Section: Resultssupporting
confidence: 54%
“…In recent work, we have shown that such monolayers are compatible with photonic applications [34,35], and in this paper we present results and discuss on monolayer quality improvement. An important point in this paper is to highlight the utility of such monolayers with ease preparation and high coverage ratio, over large area and with high stability, reliable for the final laser engineered photonic structures and throughout the overall fabrication process.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The intensity of phonon peaks can be directly related to the density of chemical bonds associated with the respective vibrations, as we do not observe a measurable increase in surface roughness of silica substrate upon implantation which has been reported to affect the Raman intensity. 17 When Er is present in the SiO 2 matrix in addition to the excess Si, the spectral increase observed in zone 2 indicates that more Si-Si bonding occurs in this sample. In other words, this indicates that the presence of Er promotes the nucleation of Si-nc.…”
Section: Resultsmentioning
confidence: 87%